Sources and transport of fluid and heat at the newly-developed Theistareykir Geothermal Field, Iceland - Saby, Marion; Pinti, Daniele L.; van Hinsberg, Vincent; Gautason, Bjarni; Sigurðardóttir, Ásgerður; Castro, Clara; Hall, Chris; Óskarsson, Finnbogi; Rocher, Océane; Hélie, Jean-François; Méjean, Pauline (Journal of Volcanology and Geothermal Research, 2020)
International audience Successful management of geothermal energy requires detailed understanding of physical and chemical conditions within the field prior to exploitation. It is thus crucial to identify fluids involved and their residence times, as well as the heat source, so as to assess the potential of the resource in terms of energy production. To this end, a geochemical study of relatively undisturbed fluids from the newly-developed Theistareykir geothermal field, Northern Volcanic Zone, Iceland was carried out on production wells, fumaroles, and mud pots. Noble gas (He, Ne, Ar, Kr, and Xe) elemental and isotopic abundances and stable isotopes (δ 18 O and δ 2 H) were measured to determine the system fluid sources and dynamics as exploitation proceeds. Results of this study, together with previously published data, show that four fluid sources are present: modern and local meteoric water (48.9%); sub-modern meteoric water from regional highlands precipitation (10.6%); pre-Holocene glaciated meteoric water (40.4%) with strongly depleted δ 2 H values of -127‰, calculated 40 K- 40 Ar* fluid residence times from 57 ± 20 ka to 92 ± 30 ka and a (U/Th)- 4 He fluid residence times from 96 ± 50 ka to 160 ± 80 ka; and, finally, 3 He-rich magmatic fluids. Concomitant enrichment in 18 O and radiogenic 4 He suggests that some fluids reside a long time in the reservoir, exchanging O and He with reservoir rocks. Maximum estimated helium isotopic ratios, 3 He/ 4 He (R), of 11.45 Ra (Ra = atmospheric ratio) show that the magma beneath Theistareykir is a depleted mid-ocean ridge basalt (MORB) mantle (DMM), with less influence (8.7 to 12.7%) of the Icelandic mantle plume source. Calculated heat (Q)/ 3 He ratios plotted vs. R/Ra and 4 He/ 36 Ar ratios suggest that convective heat transport dominates the eastern part of the field where the magmatic heat source is located, while in other parts of the field, heat conduction seems to be dominant. Boiling and phase separation exists in the field, as indicated by δ 18 O values ...